PENERAPAN MODEL PEMBELAJARAN THINK-PAIR-SHARE DENGAN MIND MAPPING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS MURID KELAS VIII A SEKOLAH PALEMBANG HARAPAN [THE IMPLEMENTATION OF THE THINK-PAIR-SHARE LEARNING MODEL WITH MIND MAPPING TO IMPROVE GRADE 8-A STUDENTS’ UNDERSTANDING OF MATHEMATICAL CONCEPTS AT SEKOLAH PALEMBANG HARAPAN] - Felix Yojinato; Dylmoon Hidayat (Universitas Pelita Harapan, 2020)
Helping students to have good conceptual understanding is one of the purposes of learning mathematics. During class observations the researchers found some students still struggling with mathematics conceptual understanding. This research implemented the Think-Pair-Share (TPS) learning model along with mind mapping as an effort to improve students’ conceptual understanding of mathematics. The research was conducted with four students of grade VIII A using Classroom Action Research (CAR) at Sekolah Palembang Harapan in 3 cycles. Each cycle consisted of 5 stages. The researcher used four instruments: quiz, the mentor's observation sheet, the mentor’s feedback, and journal reflection. The result showed that the implementation of TPS with mind mapping improved the students’ understanding of mathematical concepts.BAHASA INDONESIA ABSTRAK: Membantu siswa untuk memiliki pemahaman konsep yang baik adalah salah satu tujuan pembelajaran matematika. Selama melakukan pengamatan proses pembelajaran di kelas, peneliti menemukan bahwa siswa masih bergumul dengan pemahaman konsep matematika. Penelitian ini bertujuan menerapkan model belajar Think-Pair-Share (TPS) dengan Mind Mapping untuk meningkatkan pemahaman siswa tentang konsep matematika. Penelitian Tindakan Kelas ini dilakukan kepada 4 murid kelas VIII A Sekolah Palembang Harapan dengan 3 siklus. Tiap siklus terdiri dari 5 tahapan. Data dikumpulkan dengan menggunakan empat instrumen yaitu kuis, lembar observasi guru mentor, umpan balik guru mentor dan jurnal refleksi. Hasil penelitian menunjukkan bahwa TPS dengan Mind Mappingmeningkatkan pemahaman siswa tentang konsep matematika.